(untitled) (Journal of Informatics Education and Research, 2024)
This study investigates the investment behaviors of Indian women, with a particular focus on gold as a safe haven asset. Gold has long been embedded in the cultural and economic fabric of India, serving as both a symbol of wealth and a reliable financial safeguard. The research explores the multifaceted reasons behind the preference for gold among Indian women, examining cultural traditions, economic factors, and psychological motivations that drive this investment choice. Through a detailed analysis of secondary data and a comprehensive literature review, the study highlights how gold is utilized not only as a store of value during economic instability but also as an essential component of personal and familial wealth. Additionally, the research evaluates the shift towards modern gold investment options, such as Gold ETFs and Sovereign Gold Bonds, weighing their benefits and drawbacks compared to traditional physical gold. The findings provide insights into the enduring appeal of gold as a strategic investment for Indian women and its role in their broader financial planning.